Financial Market Enforcement in France - Laure de Batz (Prague University of Economics and Business, Faculty of International Relations (FIR), 2022)
This paper puts into perspective enforcement as conducted by the French Financial Market Authority since its creation in 2003 until 2021 with regards to the current state of the literature on financial crimes. We survey exhaustively the three main channels of action: sanctions, settlements (since 2012), and alerts (since 2010). The sample is comprised of 392 sanctions standing for cumulated 365 million euros of fines of 86 settlements standing for cumulated 13 million euros of fines, and of 194 alerts. The analyses stress the complex challenges of information acquisition regarding financial crimes, despite increased efforts of enforcers in terms of transparency. Financial innovations and internationalization of financial markets also contribute to challenge enforcement. The ultimate goal of this survey is to fuel regulatory debates on how to enforce financial regulations more efficiently in light of the recent history, in a European and globalized context.
Keywords: G18; G28; G38; K23; K41; K42; 330; Financial Crime; Financial Fraud; Financial Misconduct; White-Collar Crime; Regulation; Enforcement; Financial Markets; Information and Market Efficiency